Endoscopic ultrasound‐guided pelvic abscess drainage (with video). (26th August 2014) - Holt, Bronte; Varadarajulu, Shyam
Abstract Pelvic abscesses present a serious and challenging management problem. Endoscopic ultrasound (EUS)‐guided drainage provides a safe and effective minimally invasive treatment option. The likelihood of a successful outcome is dependent on appropriate patient selection, drainage technique and postoperative management. This review outlines the evidence behind and procedural steps required for EUS‐guided pelvic abscess drainage.